Spinning process of hydrophilic super-imitation cotton continuous polymerization polyester yarn

By adding specific ingredients and processing steps to the spinning process of polyester wire, the poor hydrophilic and static problems of polyester wire are solved, and polyester wire with high hydrophilic and breathability, anti-static and soft comfort are achieved.

CN119877140APending Publication Date: 2025-04-25ZHEJIANG HENGBAIHUA CHEMICAL FIBER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510102241.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing polyester wire has poor hydrophilicity and breathability, which can easily reduce the wear comfort of the fabric, and can easily cause static electricity and pilling, affecting the surface quality of the textile.

Method used

The spinning process of hydrophilic ultra-imitation cotton continuous polymerized polyester silk is adopted. The melting, spinning and stretching treatment is carried out by combining dimethyl terephthalate, ethylene glycol, modified hydroxyapatite nanowires, pore-forming agents, lauryl acrylate, antistatic particles and dispersant, and the fiber silk is treated with fucoidan composite liquid during the stretching process.

Benefits of technology

The hydrophilic breathability and anti-static effect of polyester wire is improved, while the flexibility and ductility of fiber wire is enhanced, the softness and comfort of fiber wire is improved, the fracture rate is reduced, and the molding effect of fiber wire is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005254483990000081
    Figure BDA0005254483990000081
  • Figure BDA0005254483990000091
    Figure BDA0005254483990000091
Patent Text Reader

Abstract

The invention relates to the field of polyester yarn processing, and particularly discloses a spinning process of hydrophilic super-imitation cotton continuous polymerization polyester yarn. Comprising the following steps: S1, weighing 80-100 parts by weight of dimethyl terephthalate, 30-50 parts by weight of ethylene glycol, 2-4 parts by weight of modified hydroxyapatite nanowires, 1-3 parts by weight of a pore forming agent, 2-4 parts by weight of lauryl acrylate, 1-3 parts by weight of antistatic particles and 1-2 parts by weight of a dispersing agent, mixing and melting, and granulating to obtain polyester particles; s2, performing melt spinning on the polyester particles to obtain cellosilk; s3, stretching the cellosilk, treating the cellosilk with fucoidin complex liquid, drying and post-treating the cellosilk to obtain a finished product polyester yarn; meanwhile, the fabric has the advantages of being good in hydrophilicity and breathability, good in antistatic effect, soft and comfortable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polyester yarn processing, and more specifically, it relates to a spinning process for hydrophilic ultra-cotton-like continuous polymerized polyester yarn. Background Art

[0002] Polyester yarn, also known as polyester fiber, is a fiber-forming polymer made from purified terephthalic acid (PTA) or dimethyl terephthalate (DMT) and ethylene glycol (EG) through esterification or ester exchange and polycondensation reaction.

[0003] Polyester yarn has high strength and wear resistance, and is suitable for the preparation of ropes and industrial fabrics. Polyester yarn has good elasticity and resilience, which gives textiles a better molding effect. It also has good heat resistance and chemical resistance, which can extend the service life of polyester yarn. At the same time, polyester yarn is soft and light, and can be widely used in textiles, clothing, home furnishings and other fields.

[0004] However, polyester yarn has poor hydrophilicity and air permeability, which can easily reduce the wearing comfort of the fabric; it is also prone to static electricity and pilling, affecting the surface quality of the textile; and the feel of polyester yarn is harder than that of cotton fiber and has a poor touch.

[0005] Therefore, how to prepare a new polyester yarn that has the advantages of good hydrophilicity and air permeability, good antistatic effect, and softness and comfort is a problem to be solved. Summary of the invention

[0006] In order to prepare a new polyester yarn which has the advantages of good hydrophilicity and air permeability, good antistatic effect, and softness and comfort, the present application provides a spinning process for hydrophilic super-cotton-like continuous polymerization polyester yarn.

[0007] The present application provides a spinning process for hydrophilic ultra-cotton-like continuous polymerized polyester yarn, which adopts the following technical scheme: A spinning process of hydrophilic super-cotton-like continuous polymerized polyester yarn comprises the following steps: S1, weighing 80-100 parts of dimethyl terephthalate, 30-50 parts of ethylene glycol, 2-4 parts of modified hydroxyapatite nanowires, 1-3 parts of pore-forming agent, 2-4 parts of lauryl acrylate, 1-3 parts of antistatic microparticles, and 1-2 parts of dispersant by weight, melt-mixing, and granulating to obtain polyester microparticles; S2, melt spinning the polyester microparticles to obtain fiber filaments; S3, the fiber filaments are stretched, treated with a fucoidan composite liquid, dried, and post-treated to obtain finished polyester filaments.

[0008] By adopting the above technical scheme, dimethyl terephthalate and ethylene glycol can react with each other to generate polyester fibers, and the flexible chain segments of lauryl acrylate can be entangled with the polyester fiber molecular chains, thereby increasing the interface compatibility between lauryl acrylate and polyester fibers. The interlacing effect of the flexible chain segments of lauryl acrylate can further improve the flexibility and ductility of the polyester fibers, thereby improving the softness and comfort of the polyester fibers. In addition, the polyester fibers are less likely to break during the stretching process, thereby ensuring the molding effect of the polyester fibers.

[0009] The pore-forming agent and modified hydroxyapatite nanowires are combined. During the preparation of fiber filaments, the pore-forming agent can cause micropores in the fiber filaments. Combined with the stretching treatment, the size of the micropores is further increased. In addition, due to the filling and connecting effect of the modified hydroxyapatite nanowires, the fiber filaments are not prone to breakage during the stretching process. Combined with the enhancement of the flexibility of the fiber filaments by lauryl acrylate, it is further ensured that the fiber filaments are not prone to breakage due to stretching. At the same time, the treatment of the fucoidan composite liquid during the stretching process can further adhere to the surface of the fiber filaments to ensure the stability of the fiber filaments, so that the fiber filaments have certain micropores and are not prone to breakage. The presence of micropores and the hydrophilic effect of the hydroxyl and carboxyl groups in the fucoidan improve the hydrophilic air permeability of the polyester filaments.

[0010] The antistatic particles and fucoidan work together. Fucoidan can reduce the accumulation of static charge on the surface of polyester yarn, and cooperate with the antistatic effect of the antistatic particles to further improve the antistatic effect of polyester yarn.

[0011] Preferably, the modified hydroxyapatite nanowires are prepared from hydroxyapatite nanowires and cetearyl alcohol melt in a mass ratio of 1:0.5-1, and the average length of the hydroxyapatite nanowires is 300-500 nm.

[0012] By adopting the above technical scheme, the viscosity of the cetearyl alcohol melt is utilized to facilitate adhesion to the surface of the hydroxyapatite nanowire; the length of the hydroxyapatite nanowire is limited, and the ultra-long hydroxyapatite nanowire has good flexibility. The higher fatty acid ester molecules of cetearyl alcohol are utilized to penetrate into the interior of the fiber molecular chain to increase the flexibility of the fiber molecular chain, improve the softness of the polyester yarn, and reduce the breakage rate of the polyester yarn; and the hydroxyl groups on the surface of the hydroxyapatite and the hydroxyl groups in the cetearyl alcohol further improve the hydrophilic effect of the polyester yarn, so that the polyester yarn has the advantage of good hydrophilicity; at the same time, the presence of cetearyl alcohol has a certain lubricating effect, and its hydrophilic hydroxyl groups are combined to improve the antistatic effect of the polyester yarn.

[0013] Preferably, the antistatic particles are composed of polyethylenediamine-modified carbon nanotubes and zinc oxide in a mass ratio of 1:0.5-1.

[0014] By adopting the above technical scheme, polyethylenediamine-modified carbon nanotubes and zinc oxide are matched, and the polyethylenediamine-modified carbon nanotubes have a porous structure, and their porosity is used to increase the air permeability of the polyester yarn. At the same time, the introduced nitrogen element is used to adjust the electronic structure, increase the surface charge density, and improve the meteorological silica's resistance to external static electricity interference, thereby improving the antistatic effect of the polyester yarn; and the filling of zinc oxide can not only improve the stability of the fiber yarn, but also can use the antistatic effect of zinc oxide to improve the antistatic effect of the polyester yarn.

[0015] Preferably, the pore-forming agent is composed of lauryl amide and polyethylene glycol-modified porous mullite microspheres in a mass ratio of 1:0.5-1.

[0016] By adopting the above technical scheme, in the process of preparing polyester microparticles, lauramide molecules are used to penetrate between fiber filaments to further improve the flexibility of polyester filaments, and polyethylene glycol, as a polyether, can further improve the cross-linking effect of porous mullite microspheres and fiber filaments, thereby ensuring the flexibility of the fiber filaments.

[0017] In the melt spinning process, the lauramide boiling point of about 200°C is used to ensure the lauramide gasification and pore formation. At the same time, the porous mullite microspheres have a high porosity, which further causes a microporous structure to appear inside the polyester filament. However, the connection effect between the porous mullite microspheres and the fiber filaments around the microporous structure ensures the air permeability of the polyester filament while reducing the fiber breakage rate, thereby ensuring the molding effect of the finished fiber filament.

[0018] Preferably, the polyethylene glycol-modified porous mullite microspheres are prepared from porous mullite microspheres and polyethylene glycol solution in a mass ratio of 1:0.5-1.2.

[0019] By adopting the above technical scheme, the porous mullite microspheres utilize their porous structure and large specific surface area to facilitate the adsorption of polyethylene glycol solution, thereby achieving the loading of the polyethylene glycol solution in the pores and on the surface of the porous mullite microspheres, and the reaction connection of polyethylene glycol with dimethyl terephthalate and ethylene glycol further improves the dispersion stability of the porous mullite microspheres in the fiber filaments, ensuring that the fiber filaments are not prone to breakage during the stretching process, and at the same time having certain microvoids to ensure the hydrophilicity and air permeability of the fiber filaments.

[0020] Preferably, the dispersant is polyvinyl pyrrolidone.

[0021] By adopting the above technical scheme, polyvinyl pyrrolidone has good hydrophilicity. Adding it to the preparation process of polyester filaments can improve the hydrophilicity of polyester filaments, help improve the hygroscopicity, air permeability and dyeing performance of polyester filaments, making them easier to dye and print; and can increase the softness and glossiness of polyester filaments, and improve their feel and appearance quality.

[0022] In the preparation process of polyester filaments, polyvinyl pyrrolidone can also be used as a dispersant to help dyes and other additives be evenly dispersed in the polymer to avoid precipitation and aggregation; it can also form complexes with dyes to enhance the affinity between dyes and fibers and improve the uniformity and fastness of dyeing.

[0023] Preferably, the fucoidan complex liquid consists of fucoidan, aminosulfonic acid and water in a mass ratio of 1:0.2-0.5:95-110.

[0024] By adopting the above technical scheme, fucoidan and aminosulfonic acid are both soluble in water, and can form a fucoidan composite liquid with a certain viscosity, which is convenient for adhering to the surface of fiber filaments by utilizing its viscosity. The sulfonic acid group in aminosulfonic acid has a certain hydrophilicity, and fucoidan contains a high content of hydroxyl group and has a certain hydrophilicity, thereby further improving the hydrophilicity of polyester filaments; and the hydroxyl group in fucoidan is connected with the sulfonic acid group of aminosulfonic acid, thereby further improving the adhesion stability of aminosulfonic acid and fucoidan on the surface of polyester fiber filaments, thereby ensuring the hydrophilic effect of polyester filaments.

[0025] The hydrophilic groups of aminosulfonic acid and fucoidan attached to the surface of polyester filaments can increase the hydrophilicity of polyester filaments, facilitate the adsorption of moisture in the air to form a water film, thereby improving the conductivity of the surface of polyester filaments. The improvement of conductivity can promote the rapid dissipation of static charge and reduce the accumulation of static charge, thereby giving polyester filaments an antistatic effect; and aminosulfonic acid can improve the surface smoothness and flatness of polyester filaments, reduce the friction between fibers, thereby further improving the antistatic effect of polyester filaments.

[0026] Preferably, the melting temperature is 180-190°C.

[0027] Preferably, the melt spinning temperature is 280-290°C.

[0028] By adopting the above technical scheme, the temperature of the mixed melt does not reach the boiling point of lauramide, but reaches 280-290°C during the melt spinning process, so that lauramide reaches a boiling point of 200°C, completing the pore-forming effect, and generating micropores inside the polyester yarn, thereby improving the hydrophilic and breathable effect of the polyester yarn and ensuring the molding stability of the polyester yarn.

[0029] Preferably, the stretching speed is 800-1000 m / min.

[0030] By adopting the above technical solution, the appropriate stretching speed can give the molecular chains inside the fiber more time to rearrange and orient, thereby increasing the crystallinity and orientation of the fiber, and can also ensure the microporosity of the fiber while ensuring the molding effect of the fiber.

[0031] In summary, this application has the following beneficial effects: 1. Dimethyl terephthalate and ethylene glycol can react to form polyester fibers. The flexible chain segments of lauryl acrylate can entangle with the polyester fiber molecular chains, increase the interfacial compatibility between lauryl acrylate and polyester fibers, and the interlacing effect of the flexible chain segments of lauryl acrylate can further improve the flexibility and ductility of the polyester yarn, thereby improving the softness and comfort of the polyester yarn. In addition, the problem of breakage is not likely to occur during the stretching process, ensuring the molding effect of the polyester yarn.

[0032] 2. The pore-forming agent and modified hydroxyapatite nanowires are combined. During the preparation of fiber filaments, the pore-forming agent can make the fiber filaments produce micropores. Combined with the stretching treatment, the size of the micropores can be further increased. In addition, the filling and connecting effect of the modified hydroxyapatite nanowires is utilized, so that the fiber filaments are not prone to breakage during the stretching process. Combined with the enhancement of the flexibility of the fiber filaments by lauryl acrylate, it is further ensured that the fiber filaments are not prone to breakage during stretching. At the same time, the treatment of the fucoidan composite liquid during the stretching process can further adhere to the surface of the fiber filaments to ensure the stability of the fiber filaments, so that the fiber filaments have certain micropores and are not prone to breakage. The presence of micropores and the hydrophilic effect of the hydroxyl and carboxyl groups in the fucoidan improve the hydrophilic air permeability of the polyester filaments. DETAILED DESCRIPTION

[0033] The present application is further described in detail below with reference to the embodiments.

[0034] Preparation example of modified hydroxyapatite nanowires The following raw materials are all commercially available.

[0035] Preparation Example 1: Modified hydroxyapatite nanowires are prepared by the following method: Heat cetearyl alcohol to 60°C and completely melt it to obtain a cetearyl alcohol melt; 0.8 kg of cetearyl alcohol melt was evenly sprayed on the surface of 1 kg of hydroxyapatite nanowires, the average length of the hydroxyapatite nanowires was 400 nm, and the average diameter was 10 nm. The hydroxyapatite nanowires were dried and dispersed until they did not stick to each other and agglomerated, thereby obtaining finished modified hydroxyapatite nanowires.

[0036] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: Heat cetearyl alcohol to 60°C and completely melt it to obtain a cetearyl alcohol melt; 0.5 kg of cetearyl alcohol melt was evenly sprayed on the surface of 1 kg of hydroxyapatite nanowires, the average length of the hydroxyapatite nanowires was 500 nm, and the average diameter was 10 nm. The hydroxyapatite nanowires were dried and dispersed until they did not stick to each other and agglomerated, thereby obtaining finished modified hydroxyapatite nanowires.

[0037] Preparation Example 3: This preparation example differs from Preparation Example 1 in that: Heat cetearyl alcohol to 60°C and completely melt it to obtain a cetearyl alcohol melt; 1 kg of cetearyl alcohol melt was evenly sprayed on the surface of 1 kg of hydroxyapatite nanowires, the average length of the hydroxyapatite nanowires was 300 nm, and the average diameter was 10 nm. The hydroxyapatite nanowires were dried and dispersed until they did not stick to each other and agglomerated, thereby obtaining finished modified hydroxyapatite nanowires.

[0038] Preparation example of polyethylenediamine modified carbon nanotubes The following raw materials are all commercially available.

[0039] Preparation Example 4: Polyethylenediamine-modified carbon nanotubes are prepared by the following method: 1 kg of carbon nanotubes was added to 10 kg of polyethylenediamine solution, the average particle size of the carbon nanotubes was 100 nm, the polyethylenediamine solution was a polyethylenediamine aqueous solution with a mass fraction of 1%, ultrasonic dispersion was performed at 20 kHz for 10 minutes, and then the liquid polyethylenediamine solution was filtered out and dried to obtain finished polyethylenediamine-modified carbon nanotubes.

[0040] Preparation Example 5: This preparation example differs from Preparation Example 4 in that: 1 kg of carbon nanotubes was added to 10 kg of polyethylenediamine solution, the average particle size of the carbon nanotubes was 80 nm, the polyethylenediamine solution was a polyethylenediamine aqueous solution with a mass fraction of 1%, ultrasonic dispersion was performed at 20 kHz for 10 minutes, and then the liquid polyethylenediamine solution was filtered out and dried to obtain finished polyethylenediamine-modified carbon nanotubes.

[0041] Preparation Example 6: This preparation example differs from Preparation Example 4 in that: 1 kg of carbon nanotubes was added to 10 kg of polyethylenediamine solution, the average particle size of the carbon nanotubes was 150 nm, the polyethylenediamine solution was a polyethylenediamine aqueous solution with a mass fraction of 1%, ultrasonic dispersion was performed at 20 kHz for 10 minutes, and then the liquid polyethylenediamine solution was filtered out and dried to obtain finished polyethylenediamine-modified carbon nanotubes.

[0042] Preparation example of polyethylene glycol modified porous mullite microspheres The following raw materials are all commercially available.

[0043] Preparation Example 7: Polyethylene glycol-modified porous mullite microspheres were prepared by the following method: 1 kg of polyethylene glycol solution is evenly sprayed on the surface of 1 kg of porous mullite microspheres, wherein the polyethylene glycol solution is a polyethylene glycol aqueous solution with a mass fraction of 1%, the polyethylene glycol is polyethylene glycol 8000, the average porosity of the porous mullite microspheres is 20%, and the average particle size of the porous mullite microspheres is 200 nm. The porous mullite microspheres are dried and dispersed until the porous mullite microspheres do not stick to each other and agglomerate to obtain a finished product.

[0044] Preparation Example 8: This preparation example differs from Preparation Example 7 in that: 0.5 kg of polyethylene glycol solution is evenly sprayed on the surface of 1 kg of porous mullite microspheres, the polyethylene glycol solution is a polyethylene glycol aqueous solution with a mass fraction of 1%, the polyethylene glycol is polyethylene glycol 8000, the average porosity of the porous mullite microspheres is 20%, and the average particle size of the porous mullite microspheres is 200 nm. The porous mullite microspheres are dried and dispersed until the porous mullite microspheres do not stick to each other and agglomerate to obtain a finished product.

[0045] Preparation Example 9: This preparation example differs from Preparation Example 7 in that: 1.2 kg of polyethylene glycol solution is evenly sprayed on the surface of 1 kg of porous mullite microspheres, wherein the polyethylene glycol solution is a polyethylene glycol aqueous solution with a mass fraction of 1%, the polyethylene glycol is polyethylene glycol 8000, the average porosity of the porous mullite microspheres is 20%, and the average particle size of the porous mullite microspheres is 200 nm. The porous mullite microspheres are dried and dispersed until the porous mullite microspheres do not stick to each other and agglomerate to obtain a finished product.

[0046] Preparation Example of Fucoidan Complex Liquid The following raw materials are all commonly available on the market.

[0047] Preparation Example 10: The fucoidan complex solution was prepared by the following method: 1 kg of fucoidan and 0.4 kg of aminosulfonic acid were placed in 100 kg of water and stirred until the fucoidan and aminosulfonic acid were completely dissolved to obtain a fucoidan complex liquid.

[0048] Preparation Example 11: This preparation example differs from Preparation Example 10 in that: 1 kg of fucoidan and 0.2 kg of aminosulfonic acid were placed in 95 kg of water and stirred until the fucoidan and aminosulfonic acid were completely dissolved to obtain a fucoidan composite liquid.

[0049] Preparation Example 12: This preparation example differs from Preparation Example 10 in that: 1 kg of fucoidan and 0.5 kg of aminosulfonic acid were placed in 110 kg of water and stirred until the fucoidan and aminosulfonic acid were completely dissolved to obtain a fucoidan complex liquid. Example

[0050] The following raw materials are all commercially available.

[0051] Embodiment 1: A spinning process of hydrophilic ultra-cotton-like continuous polymerized polyester yarn: S1. Weigh 90 kg of dimethyl terephthalate, 40 kg of ethylene glycol, 3 kg of modified hydroxyapatite nanowires, 2 kg of pore-forming agent, 3 kg of lauryl acrylate, 2 kg of antistatic microparticles, and 1.5 kg of dispersant by weight, heat to 180 ° C for melt mixing, and then granulate by extrusion to obtain polyester microparticles. The average particle size of the polyester microparticles is 40 μm; the modified hydroxyapatite nanowires are the modified hydroxyapatite nanowires prepared in Preparation Example 1; the pore-forming agent is composed of lauramide and polyethylene glycol-modified porous mullite microspheres prepared in Preparation Example 7 in a mass ratio of 1:1; the antistatic microparticles are composed of polyethylenediamine-modified carbon nanotubes prepared in Preparation Example 4 and zinc oxide in a mass ratio of 1:1, and the average particle size of the zinc oxide is 80 nm; the dispersant is polyvinyl pyrrolidone; S2, melt spinning the polyester microparticles at 280° C. to obtain fiber filaments; S3. The fiber filaments are stretched at 180°C and a stretching speed of 1000 m / min with a stretching multiple of 3. After stretching, they are immersed in the fucoidan composite liquid prepared in Preparation Example 11 while hot for 3 seconds, and then the excess liquid is drained off. The fiber filaments are further stretched by 0.5 times to complete the stretching. After drying and surface polishing, a finished polyester filament with a smooth surface is obtained.

[0052] Embodiment 2: This embodiment differs from Embodiment 1 in that: S1. Weigh 80 kg of dimethyl terephthalate, 20 kg of ethylene glycol, 2 kg of modified hydroxyapatite nanowires, 1 kg of pore-forming agent, 2 kg of lauryl acrylate, 1 kg of antistatic microparticles, and 1 kg of dispersant by weight, heat to 180 ° C for melt mixing, and then granulate by extrusion to obtain polyester microparticles; the modified hydroxyapatite nanowires are the modified hydroxyapatite nanowires prepared in Preparation Example 2; the pore-forming agent is composed of lauramide and polyethylene glycol-modified porous mullite microspheres prepared in Preparation Example 8 in a mass ratio of 1:0.5; the antistatic microparticles are composed of polyethylenediamine-modified carbon nanotubes prepared in Preparation Example 5 and zinc oxide in a mass ratio of 1:0.5; S2, melt spinning the polyester microparticles at 280° C. to obtain fiber filaments; S3. The fiber filaments are stretched at 180°C and a stretching speed of 1000 m / min with a stretching multiple of 3. After stretching, they are immersed in the fucoidan composite liquid prepared in Preparation Example 11 while hot for 3 seconds, and then the excess liquid is drained off. The fiber filaments are further stretched by 0.5 times to complete the stretching. After drying and surface polishing, a finished polyester filament with a smooth surface is obtained.

[0053] Embodiment 3: This embodiment differs from Embodiment 1 in that: S1. Weigh 100 kg of dimethyl terephthalate, 50 kg of ethylene glycol, 4 kg of modified hydroxyapatite nanowires, 3 kg of pore-forming agent, 4 kg of lauryl acrylate, 3 kg of antistatic microparticles, and 2 kg of dispersant by weight, heat to 190 ° C for melt mixing, and then granulate by extrusion to obtain polyester microparticles; the modified hydroxyapatite nanowires are the modified hydroxyapatite nanowires prepared in Preparation Example 3; the pore-forming agent is composed of lauramide and polyethylene glycol-modified porous mullite microspheres prepared in Preparation Example 9 in a mass ratio of 1:1; the antistatic microparticles are composed of polyethylenediamine-modified carbon nanotubes prepared in Preparation Example 6 and zinc oxide in a mass ratio of 1:1; S2, melt spinning the polyester microparticles at 290° C. to obtain fiber filaments; S3. The fiber filaments are stretched at 180°C and a stretching speed of 1000 m / min with a stretching multiple of 3 times. After stretching, they are immersed in the fucoidan composite liquid prepared in Preparation Example 12 while hot for 3 seconds, and then the excess liquid is drained off. The fiber filaments are further stretched by 0.5 times to complete the stretching. After drying and surface polishing, a finished polyester filament with a smooth surface is obtained.

[0054] Embodiment 4: This embodiment differs from Embodiment 1 in that: No cetearyl alcohol melt was added during the preparation of modified hydroxyapatite nanowires.

[0055] Embodiment 5: This embodiment differs from Embodiment 1 in that: The antistatic particles are substituted with silicon dioxide microspheres of equal mass for the polyethylenediamine-modified carbon nanotubes, and the average particle size of the silicon dioxide microspheres is 500 nm.

[0056] Embodiment 6: This embodiment differs from Embodiment 1 in that: No lauramide was added to the pore former.

[0057] Embodiment 7: This embodiment differs from Embodiment 1 in that: The pore-forming agent is to replace the polyethylene glycol-modified porous mullite microspheres with mullite microspheres of the same mass.

[0058] Embodiment 8: This embodiment differs from Embodiment 1 in that: During the preparation of the fucoidan complex solution, no aminosulfonic acid was added.

[0059] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: No modified hydroxyapatite nanowires were added to the raw materials.

[0060] Comparative Example 2: The difference between this comparative example and Example 1 is that: No lauryl acrylate is added to the raw materials.

[0061] Comparative Example 3: The difference between this comparative example and Example 1 is that: No fucoidan complex liquid was added to the raw materials.

[0062] Performance testing 1. Hydrophilic air permeability test The polyester yarns were prepared by the methods of Examples 1-8 and Comparative Examples 1-3 respectively, and the polyester yarns were spun to obtain textiles. The specification of the textiles was 180 g / m 2 ; Refer to GB / T21655.1-2008 to test its moisture permeability and record the data; the higher the moisture permeability, the better the air permeability; The contact angle of the textile is also tested. The smaller the contact angle, the better the hydrophilicity.

[0063] 2. Antistatic effect detection The polyester yarns were prepared by the methods of Examples 1-6, 8 and Comparative Example 3, and the polyester yarns were spun to obtain textiles. The specification of the textiles was 180 g / m 2 ; Test the static voltage half-life according to GB / T12703.1-2008 and record the data.

[0064] 3. Softness test The polyester yarns were prepared by the methods of Examples 1-7 and Comparative Example 2, and the polyester yarns were spun to obtain textiles. The specification of the textiles was 180 g / m 2 ; Refer to GB / T8942-2016 to test the softness. The smaller the softness value, the softer it is. Record the data.

[0065] Table 1 Performance test table (“ / ” in the table means that the corresponding embodiment or comparative example did not test the item, so there is no data) It can be seen from Examples 1-3 and Table 1 that the polyester yarn prepared in the present application has good hydrophilic air permeability and antistatic effect, and has a certain degree of softness and comfort.

[0066] Combining Example 1 and Examples 4-8 and Table 1, it can be seen that no cetearyl alcohol solution was added during the preparation of the modified hydroxyapatite nanowires in Example 4. Compared with Example 1, the hydrophilic air permeability of the polyester yarn prepared in Example 4 is worse than that in Example 1, the antistatic effect is worse than that in Example 1, and the softness is worse than that in Example 1; this indicates that cetearyl alcohol has a hydrophilic group that facilitates improving the hydrophilic air permeability of the polyester yarn, and that cetearyl alcohol can improve the antistatic effect and softness of the polyester yarn.

[0067] In the antistatic particles of Example 5, the polyethylenediamine-modified carbon nanotubes are replaced with silica microspheres of equal mass, and the average particle size of the silica microspheres is 500 nm. Compared with Example 1, the contact angle of Example 5 is greater than that of Example 1, the moisture permeability is lower than that of Example 1, the half-life is greater than that of Example 1, and the softness is worse than that of Example 1; this indicates that the polyethylenediamine-modified carbon nanotubes can not only utilize the hydrophilic effect of polyethylenediamine in combination with the breathable effect of carbon nanotubes to improve the hydrophilic and breathable properties of polyester yarns, but also have a certain antistatic effect, and at the same time, polyethylenediamine can ensure the softness of the polyester yarn.

[0068] No lauramide is added to the pore-forming agent of Example 6. Compared with Example 1, the contact angle of Example 6 is greater than that of Example 1, the moisture permeability is lower than that of Example 1, the half-life is greater than that of Example 1, and the softness is worse than that of Example 1. This indicates that lauramide has a partial pore-forming effect under the conditions of hot-melt spinning, and lauramide contains a hydrophilic group, which further improves the hydrophilicity of the polyester yarn, and at the same time has a certain softness and antistatic effect.

[0069] The pore-forming agent of Example 7 is to replace the polyethylene glycol-modified porous mullite microspheres with mullite microspheres of equal mass. Compared with Example 1, the contact angle of Example 7 is greater than that of Example 1, the moisture permeability is lower than that of Example 1, and the softness is worse than that of Example 1. This indicates that the polyethylene glycol-modified porous mullite particles utilize the porous effect of the porous mullite microspheres, combined with the connecting effect of polyethylene glycol and dimethyl terephthalate, to further improve the softness of the polyester yarn.

[0070] During the preparation of the fucoidan composite liquid in Example 8, aminosulfonic acid was not added. Compared with Example 1, the contact angle of Example 8 was greater than that of Example 1, the moisture permeability was lower than that of Example 1, and the half-life was greater than that of Example 1. This indicates that aminosulfonic acid has a certain hydrophilicity, and combined with fucoidan, the hydrophilic and air permeability of the polyester fiber surface is improved, and aminosulfonic acid has a certain antistatic effect.

[0071] Combining Example 1 and Comparative Examples 1-3 and Table 1, it can be seen that no modified hydroxyapatite nanowires are added to the raw materials of Comparative Example 1. Compared with Example 1, the contact angle of Comparative Example 1 is greater than that of Example 1, and the moisture permeability is lower than that of Example 1; this indicates that the modified hydroxyapatite nanowires have a certain filling effect and cooperate with the hydrophilic permeability of cetearyl alcohol to further improve the hydrophilic and breathable effect of the polyester yarn.

[0072] No lauryl acrylate was added to the raw materials of Comparative Example 2. Compared with Example 1, the contact angle of Comparative Example 2 was greater than that of Example 1, the moisture permeability was lower than that of Example 1, and the softness was worse than that of Example 1; this indicated that the lauryl acrylate flexible chain segment could be intercalated inside the fiber filaments to improve the softness of the fiber filaments, and utilize its hydrophilic base to improve the hydrophilic air permeability of the polyester filaments.

[0073] In Comparative Example 3, no fucoidan composite liquid was added to the raw materials. Compared with Example 1, the contact angle of Comparative Example 3 was greater than that of Example 1, and the half-life was greater than that of Example 1, indicating that fucoidan has a good hydrophilic effect and a certain antistatic effect.

[0074] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A spinning process for hydrophilic ultra-cotton-like continuous polymerized polyester yarn, characterized in that: The steps include: S1, weighing 80-100 parts of dimethyl terephthalate, 30-50 parts of ethylene glycol, 2-4 parts of modified hydroxyapatite nanowires, 1-3 parts of pore-forming agent, 2-4 parts of lauryl acrylate, 1-3 parts of antistatic microparticles, and 1-2 parts of dispersant by weight, melt-mixing, and granulating to obtain polyester microparticles; S2, melt spinning the polyester microparticles to obtain fiber filaments; S3, the fiber filaments are stretched, treated with a fucoidan composite liquid, dried, and post-treated to obtain finished polyester filaments.

2. The spinning process of a hydrophilic super-cotton-like continuous polymerized polyester yarn according to claim 1, characterized in that: The modified hydroxyapatite nanowires are prepared from hydroxyapatite nanowires and cetearyl alcohol melt in a mass ratio of 1:0.5-1, and the average length of the hydroxyapatite nanowires is 300-500nm.

3. The spinning process of a hydrophilic super-cotton-like continuous polymerized polyester yarn according to claim 1, characterized in that: The antistatic particles are composed of polyethylenediamine-modified carbon nanotubes and zinc oxide in a mass ratio of 1:0.5-1.

4. The spinning process of a hydrophilic super-cotton-like continuous polymerized polyester yarn according to claim 1, characterized in that: The pore-forming agent is composed of lauryl amide and polyethylene glycol-modified porous mullite microspheres in a mass ratio of 1:0.5-1.

5. The spinning process of a hydrophilic ultra-cotton-like continuous polymerized polyester yarn according to claim 4, characterized in that: The polyethylene glycol-modified porous mullite microspheres are prepared from porous mullite microspheres and polyethylene glycol solution in a mass ratio of 1:0.5-1.

2.

6. The spinning process of a hydrophilic super-cotton-like continuous polymerized polyester yarn according to claim 1, characterized in that: The dispersant is polyvinyl pyrrolidone.

7. The spinning process of a hydrophilic super-cotton-like continuous polymerized polyester yarn according to claim 1, characterized in that: The fucoidan complex liquid consists of fucoidan, aminosulfonic acid and water in a mass ratio of 1:0.2-0.5:95-110.

8. The spinning process of a hydrophilic ultra-cotton-like continuous polymerized polyester yarn according to claim 1, characterized in that: The temperature of the melt mixing is 180-190°C.

9. The spinning process of a hydrophilic super-cotton-like continuous polymerized polyester yarn according to claim 1, characterized in that: The temperature of the melt spinning is 280-290°C.

10. The spinning process of a hydrophilic super-cotton-like continuous polymerized polyester yarn according to claim 1, characterized in that: The stretching speed is 800-1000 m / min.